PWE-088 Negative lower GI investigations: miss rates in colorectal cancer. (28th May 2012) - To, L; Mills, S; Townsend, T; Leiper, K
Abstract : Introduction: Retrospective studies have confirmed that colonic investigations may miss a diagnosis of colorectal cancer (CRC) with a wide variation in reported miss rates. 1 2 Colorectal cancer miss rates of up to 12%, 22% and 50% have been reported for colonoscopy, barium enema and sigmoidoscopy, respectively. Methods: A retrospective study was conducted to determine the diagnostic miss rate of colorectal cancer at our institution. All patients diagnosed with colonic or rectal adenocarcinoma between 2006 and 2010 were identified from the Royal Liverpool and Broadgreen University Hospital Trust histopathology database. Data were collected using the computerised systems and case notes. A miss was defined as a patient investigated with barium enema (BE), CT abdo-colon enhanced (CTACE), CT colonoscopy (CTC), flexible sigmoidoscopy and/or colonoscopy, and discharged without being followed-up or diagnosed with CRC in the 5 years preceding the subsequent CRC diagnosis. Results: During the study period, 579 patients were diagnosed with colorectal cancer. The notes were irretrievable or had insufficient documentation in 5 cases. Twenty-two (3.8%) cases were considered misses: 5 (0.8%) were administrative misses, where patients were lost to follow-up, or they cancelled or failed to attend an appointment; in one case (0.2%), there was a clinician-associated miss, where an inappropriate choice of investigation was performed (a flexible sigmoidoscopy missed a proximal CRC); and 16 (2.8%) were technical misses, where CRC was missed with an appropriate choice of investigation. Of the technical misses, 10 (1.7%) were radiological (0.7%, 0.7% and 0.3% for BE, CTACE and CTC respectively) and 8 (1.4%) were endoscopic (0.5% and 0.9% for flexible sigmoidoscopy and colonoscopy). 45% of missed cancers were left-sided and below the splenic flexure. Conclusion: This study has shown a lower miss rate in our institution than previously reported, 3 and when compared with other studies. Competing interests: None declared. References: 1. Frenette CT, Strum WB. Relative rates of missed diagnosis for colonoscopy, barium enema, and flexible sigmoidoscopy in 379 patients with colorectal cancer. J Gastrointest Cancer 2007;38 :148–53. 2. Somasekar A, James L, Stephenson BM, et al. The value of auditing negative lower GI investigations preceding a final diagnosis of colorectal cancer. Colorectal Dis 2009;11 :740–4. 3. Graham M, et al. Endoscopy 2005;37 :A275.